Analyzing Effective Tax Rate Variability in Indonesian State-Owned Banks: Evidence from 2020–2024 - Annisa Amalia; Dwi Martani (Greenation International Journal of Economics and Accounting, 2025)
This study examines the variability of the effective tax rate (ETR) in state-owned banks (BUMN) during the 2020–2024 tax years, with a case study focused on BANK XYZ. The objective of the study is to evaluate the variability of ETR and the influencing factors in state-owned banks, as well as to assess how BANK XYZ manages its ETR. The methodology employed includes quantitative analysis of financial statement data from BUMN banks, combined with interviews conducted with the tax and finance managers of BANK XYZ. The findings reveal that permanent differences affect the GAAP ETR, while both temporary and permanent differences influence the Current ETR. Among the three tax rate proxies, GAAP ETR demonstrates the most stable value and is closest to the statutory rate of 22%, whereas Cash ETR and Current ETR exhibit greater fluctuations. A common temporary difference observed across the banks is depreciation expense, while the most dominant permanent difference arises from non-deductible expenses. Additionally, income from subsidiaries contributes to the increased variability of the ETR. BANK XYZ reports an ETR that exceeds the statutory rate. Based on interview results, BANK XYZ maintains fiscal compliance while optimizing cash flow through tax management. The bank continues to enhance its tax governance through the utilization of technology, regular regulatory assessments, and strengthened collaboration with external tax consultants.